The Effect of Spiritual Therapy Listening to Morattal Al-Qur'an Surah Ar-Rahman on Student Anxiety at STIKES Cirebon 2024 - Sutarna, Agus; Indragiri, Suzana; Maulana, Sidik Abi (Indo Consultan Energi, 2025)
Students who are completing their final assignments can experience anxiety. One effort to reduce the anxiety level of students preparing their final assignments is by listening to Murottal Al-Qur'an. The purpose of this study was to determine the effect of spiritual therapy listening to mutual Al-Qur'an Surah Ar-Rahman on the anxiety of final-year nursing undergraduate students at STIKes Cirebon. This study used a quasi-experimental research method with a one-group pretest-posttest design. The sample in this study was 48 respondents. The data analysis technique used was the Wilcoxon test. The study results have a ρ value 0.000 (ρ <0.05). This means that H0 failed to be rejected, meaning spiritual therapy listening to Murottal Al-Qur'an Surah Ar-Rahman can reduce anxiety levels in final-year nursing undergraduate students at STIKES Cirebon 2024. The results of this study can be used as a source of information to increase knowledge about the effect of spiritual therapy by listening to Murottal Al-Qur'an. Al-Qur'an stimulants are superior to other hearing therapies because they can produce delta waves to reduce anxiety.